Vanishing White Matter Disease- Report of two Cases - Kundu, Gopen Kumar; Islam, Rumana; Saba, Noor A (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Vanishing white matter (VWM) disease is a chronic progressive childhood onset leukodystrophy that result in central nervous system demyelination, often precipitated by some stressful events. There is wide phenotypic variation buy typical MRI findings are diagnostic in most of the patients. Here we report two cases of vanishing white matter disease with typical MRI findings. J Bangladesh Coll Phys Surg 2022; 40: 314-317